The Benefits of Defoliation (Eurasian Journal of Engineering and Technology, 2022)
The new Ento-Dephol showed a higt result, when guza couses open 50-60% while using 0,15 litres of defoliation for each hectar in order to defoliante cotton artificially.6,0 litres use of defoliation gave better result regarding to the other alternatives.